Institutional effects on developing political capabilities: the case of European airlines on the aftermarth of 9/11 - Rajwani, Tazeeb; Paroutis, S (Cranfield University, 2012)
Governments and their agents can both facilitate and constrain organizational wealth creation. Whilst heterogeneously distributed valuable political resources allow a firm to develop capabilities to gain competitive advantage, less attention has been devoted to the conditions that impact the development of political capabilities in varying institutional contexts. This qualitative, inductive study examines the development and application of political capabilities in five European national airline carriers within an institutional context requiring reactive political strategies to influence policy makers, i.e. avoiding security costs from 9/11. We contribute to capability theory and practice studies by showing how senior management teams develop political capabilities in institutional contexts exhibiting increased uncertainty. We argue that while the senior management's attention to specific political processes can create valuable political capabilities, this value creation is moderated by the nature of the institutional environment and its barriers.